Transforming Zakat Fatwas to Strengthen Technopreneurship and Governance in Islamic Organizations - Nasution, Erni Juliana Al Hasanah; Latief, Hilman; Rukmana, Raditya (Aptisi Transactions On Technopreneurship (ATT), 2026)
This study examines how zakat fatwa transformation provides sharia foundations for technopreneurship development and governance strengthening in Indonesia following the enactment of Law No. 23/2011. Analyzing 56 fatwas through the Tawhidi String Relations (TSR) framework, the study reveals significant insights into organizational approaches, system evolution, and implementation outcomes. The research identifies different yet complementary strategies among Islamic organizations: Muhammadiyah exhibits progressive innovation (κ = 0.88) through the Manhaj Tarjih methodology, emphasizing modern economic instruments and digital integration; NU applies the Bahtsul Masail approach, upholding classical principles while adapting to regional contexts (κ = 0.83); and MUI focuses on national standardization (κ = 0.87), effectively integrating sharia compliance with modern governance frameworks. The effectiveness of fatwa implementation improved substantially, with scores rising from 0.56 (2012–2015) to 0.82 (2020–2024), reflecting the adoption of professional zakat practices, empowerment initiatives, and digital transformation. These transformations have fostered a zakat-based technopreneurship ecosystem through digital payment integration, productive distribution for MSME development, and mustahik entrepreneurship programs. Positive impacts are evident across key dimensions: enhanced sharia compliance (0.85), improved socio-economic development (0.76), and strengthened institutional governance (0.81). The findings highlight critical policy implications: enhancing sharia compliance, developing flexible regulatory frameworks, advancing digital zakat management, and strengthening monitoring mechanisms. Overall, the study contributes to the theoretical advancement and practical application of sustainable zakat governance while promoting technopreneurship innovation within modern Islamic contexts.